PENDIDIKAN KARAKTER DALAM PAI YANG TERPINGGIRKAN OLEH FOKUS PADA HAFALAN - Cut Dewi Rahma (Yayasan An-Nur Meunara Baro, 2025)
This article critiques the prevailing tendency in Islamic Religious Education (PAI) to prioritize memorization over meaningful character formation. Employing a qualitative case study approach in various schools and madrasahs, data were collected through classroom observation, interviews with teachers, students, and parents, and curriculum document analysis. The findings reveal that over 80% of PAI instructional time is devoted to memorizing verses or hadiths, with minimal allocation for value discussions or social action. This imbalance results in a failure to internalize core Islamic values such as honesty, empathy, and cooperation among students. Notably, some cases highlight the irony of Qur’an memorizers engaging in bullying. The study identifies two main root causes: assessment systems that focus solely on memorization, and a lack of teacher training in character-based pedagogy. As a solution, the paper proposes an integrated PAI teaching model that links memorization with real-life application, along with holistic assessment that evaluates cognitive, affective, and social domains. The article underscores the need to redefine PAI's objective not merely as religious knowledge transmission, but as a transformative tool for moral education.